Efektivitas Hipnoterapi Sebagai Terapi Komplementer Untuk Menurunkan Tingkat Kecemasan: Literatur Review - Irawan, Yahya Firdaus; Rahmadhani, Diva; Azka Samsudin, Sania (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Anxiety is defined as a significant mental disorder that affects millions of people around the world, including Indonesia, with an impact on physical and psychological health. This study aims to examine the effectiveness of hypnotherapy as a complementary therapy in reducing anxiety levels through a literature review approach. The research method used is a literature review that analyzes scientific articles from indexed journal databases, namely 4 PubMed articles and 4 Google Scholar articles with publication limitations in the last 5 years. The results of the study show that hypnotherapy is effective in reducing anxiety in various age groups. Hypnotherapy utilizes hypnotic conditions through the induction of relaxation (trance) that increases the acceptance of healing suggestions in the subconscious mind, reduces motor tension, and promotes emotional calm. The success factor is determined by the client's ability to achieve a state of relaxation (trance), which makes the subconscious mind more open to healing suggestions. Hypnotherapy has been proven to be safe, well-tolerated, and beneficial, as well as effective in lowering anxiety levels